Designing AR Interfaces for Enhanced User Experience (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Augmented Reality (AR) interfaces are transforming biological education and research by providing immersive and interactive learning environments that increase user engagement and learning results. This study analyzes the use of augmented reality (AR) technology in biological sciences, highlighting the importance of User Experience (UX) design concepts in improving AR interfaces for educational effectiveness.The research provides a comprehensive overview of designing AR interfaces tailored to biological education, highlighting intuitive navigation, interactive feedback mechanisms, and personalized learning experiences. By examining current advancements and future trends in AR technology, the paper identifies key opportunities for innovation in educational settings.A poll of sixty students was conducted to collect data on demographics, AR usage experience, educational efficacy, user satisfaction, and perceived advantageous features. The data indicate that AR is well-received, with high scores for simulation realism, ease of use, and engagement.This lecture finishes by bringing together information about augmented reality's transformative potential in biology education and research. It proposes avenues for further research and development to harness the full capabilities of AR technology, shaping the future of learning in the biological sciences.